Site-dependent numerical safety analysis in microwave skin spectroscopy: comparison of monopole and vivaldi antennas - Shang, Shangyang; Popović, Milica (Frontiers in Antennas and Propagation, 2025)
Over the past decade, sensors for skin cancer detection, with operation at micro- and millimeter-wave frequency range, have been under investigation. Thus, safety concerns related to radiation exposure have become critical, especially for patients with vulnerable skin. Studies to date fell short in detailed safety assessments. Many evaluations rely on a single-tissue model representing a single anatomical site. Moreover, most studies assess safety solely via specific absorption rate (SAR) but omit the temperature-rise analysis induced by radiation exposure. In this work, we investigate two types of surface-wave-based antennas operating in the microwave band. Multilayer tissue models were constructed to emulate nine major body sites. The key safety metrics, including the SAR distribution and temperature increase, were analyzed through full-wave electromagnetic simulations in Ansys HFSS. The results reveal substantial inter-site variability in the metrics, highlighting the necessity of full-body evaluation prior to determining the overall safety measures for the new diagnostic devices. Furthermore, we derive power limits for surface-wave antennas in accordance with U.S. and Canadian safety standards, and verify their conservativeness via temperature analysis. Our findings provide a basis for a comprehensive framework for radiation safety assessment of wearable devices operating in the microwave band.